Iran - Somervill, Barbara A. (New York : Children's Press, 2012)
Describes the geography, plants and animals, history, economy, language, religions, culture, and people of Iran.
Bargaining at the bazaar -- Deserts and mountains -- Into the wild -- Through the centuries -- The first Islamic Republic -- Rich in resources -- A cultural blend -- The five pillars of Islam -- The arts and more -- Family and community.
Includes bibliographical references (p. 134-135) and index.
Keywords: Iran -- Juvenile literature; Iran; Iran